Perubahan Penggunaan Lahan di Kecamatan Kelara dan Rumbia Kabupaten Jeneponto - Sutomo, Firman (Jurnal Ecosolum, 2019)
Land use that is incompatible with the function of land can lead to negative effects, therefore it is necessary to set the direction of land use change in land use. This study aims to determine the dynamics of land use during the period of 15 years (1999-2013) and determine the fit between the spatial patterns of spatial plans with the actual land use in Rumbia and Kelara, Jeneponto. The study was conducted through data collection and analysis of data, the data used include primary data and secondary data obtained through observation, field observations, and other supporting data. Data already collected subsequently analyzed by using descriptive and quantitative analysis by means of data interpretation and overlay maps with GIS systems. The results of the study show that obtained six classes of land use consisting of forests, gardens, settlements, rice fields, shrubs and moorings / fields indicate that land use has decreased by 2.66% in 1999, 2004 by 1, 44%, and in 2013 decreased to 1.09% and those that experienced an increase in area were fields / fields of 50.44% in 1999, in 2004 it increased to 62.10%, and in 2013 the area increased to 69.52%.